2007
DOI: 10.1021/ma0623542
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of PEM Properties of Copoly(aryl ether ether nitrile)s Containing Sulfonic Acid Bonded to Naphthalene in Structurally Different Ways

Abstract: The study represents a comparative investigation of three series of high molecular weight aromatic poly(aryl ether ether nitrile) copolymers (SPAEEN-n), containing different sulfonated naphthalene groups, where n (in the range 0-80 mol %) refers to molar percentage of repeat units containing the sulfonic acid function. The three series of SPAEEN-n copolymers were synthesized via potassium carbonate-mediated nucleophilic polycondensation reactions of commercially available monomers: 2,6-difluorobenzonitrile (2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 31 publications
2
78
0
Order By: Relevance
“…The researchers also performed a comparative study of sulfonated poly(arylene ether ether nitrile) (SPAEEN) copolymers with different sulfonic acid bonding sites (Fig. 15) [87][88][89][90], which will be further discussed in Section 2.2.1.…”
Section: Direct Copolymerization Of Sulfonated Monomersmentioning
confidence: 99%
“…The researchers also performed a comparative study of sulfonated poly(arylene ether ether nitrile) (SPAEEN) copolymers with different sulfonic acid bonding sites (Fig. 15) [87][88][89][90], which will be further discussed in Section 2.2.1.…”
Section: Direct Copolymerization Of Sulfonated Monomersmentioning
confidence: 99%
“…[4][5][6] Consequently, much progress has been made to develop novel hydrocarbon PEMs based on sulfonated aromatic polymers, which have good physical properties and are inexpensive. The most widely investigated PEMs include sulfonated derivatives of poly(arylene ether sulfone)s (SPAES), 7,8 poly-(arylene ether ether ketone)s (SPEEK), [9][10][11] poly(arylene sulfide sulfone)s (SPSS), 12,13 poly(arylene ether nitrile)s (SPAEEN), [14][15][16] polyimides (SPI), [17][18][19][20][21] and polyphenylenes (PP). [22][23][24] Many hydrocarbon polymers show sufficiently high conductivities only at high ion-exchange capacities (IEC)s, which causes extensive water uptake above a critical temperature (percolation threshold), or a dramatic loss of mechanical properties due to dimensional swelling that render them unsuitable for practical PEM applications.…”
Section: Introductionmentioning
confidence: 99%
“…Chemically and thermally stable fully aromatic hydrocarbon polymers containing pendant acidic functions are considered promising as alternative PEM materials. 2 Among recently developed polymer electrolyte membranes, sulfonated poly(arylene ether sulfone) (SPAES) and sulfonated poly(arylene ether ketone) (SPAEK) are promising. [3][4][5][6][7][8][9] Wang et al 9 reported the synthesis of biphenyl-based SPAES.…”
Section: Introductionmentioning
confidence: 99%